2022
DOI: 10.1021/jacs.1c10174
|View full text |Cite
|
Sign up to set email alerts
|

Emulating Membrane Protein Environments─How Much Lipid Is Required for a Native Structure: Influenza S31N M2

Abstract: This report investigates the homotetrameric membrane protein structure of the S31N M2 protein from Influenza A virus in the presence of a high molar ratio of lipid. The structured regions of this protein include a single transmembrane helix and an amphipathic helix. Two structures of the S31N M2 conductance domain from Influenza A virus have been deposited in the Protein Data Bank (PDB). These structures present different symmetries about the channel main axis. We present new magic angle spinning and oriented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Residual dipolar couplings (RDCs) are a sensitive probe of molecular structures in solution . In the case of an α-helical peptide with an expected kink in it, like melittin, NMR-based orientation restraints can tightly define the relative orientation of the two α-helical segments . We utilized the ARTSY technique to measure backbone 1 D NH RDCs in two separate alignment media, liquid crystalline Pf1 filamentous phage (Figure S6) and positively charged stretched polyacrylamide gel, on an 800 MHz spectrometer at 20 °C.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Residual dipolar couplings (RDCs) are a sensitive probe of molecular structures in solution . In the case of an α-helical peptide with an expected kink in it, like melittin, NMR-based orientation restraints can tightly define the relative orientation of the two α-helical segments . We utilized the ARTSY technique to measure backbone 1 D NH RDCs in two separate alignment media, liquid crystalline Pf1 filamentous phage (Figure S6) and positively charged stretched polyacrylamide gel, on an 800 MHz spectrometer at 20 °C.…”
mentioning
confidence: 99%
“…17 In the case of an α-helical peptide with an expected kink in it, like melittin, NMR-based orientation restraints can tightly define the relative orientation of the two α-helical segments. 18 We utilized the ARTSY 19 technique to measure backbone 1 D NH RDCs in two separate alignment media, liquid crystalline Pf1 filamentous phage (Figure S6) and positively charged stretched polyacrylamide gel, on an 800 MHz spectrometer at 20 °C. Pf1 has a negatively charged surface that has strongly attractive, electrostatic interactions with positively charged melittin.…”
mentioning
confidence: 99%
“…Figure 2B compares the spectrum in DPhPC with a mixture of DOPC and DOPE lipids at an LPRT of 180. These lipids were chosen to match the composition reported by Cross and coworkers, 25,26 and the LPRT of 180 was chosen to exceed the value of 120 reported in their work. 13 C, 15 N S31N M218-60 reconstitued at high and low LPRT.…”
Section: Resultsmentioning
confidence: 99%
“…Cross and coworkers reported that the difference in reported structures is caused by an insufficient amount of lipids in MAS NMR preparations. 25 The dimer of dimers structure of S31N M218-60 was determined from samples assembled with a lipid to protein tetramer ratio (LPRT) of 24. Two sets of peaks are evident in MAS NMR spectra under these conditions, which is the result of a tetramer structure composed of a dimer-of-dimers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation